sandy.beaches.ecology.cvs - Sibaja Cordero, Jeffrey Alejandro (2019)
The data were taken from 28 sandy beaches of Costa Rica (16 from the Pacific Coast and 12 from the Caribbean). This study aimed to (1) determine the differences of sediment and beach characteristics between both Pacific and Caribbean coasts and the tidal levels; (2) analyze the species richness and abundance of macrofauna considering the coasts, tidal levels, and environmental covariates (sediment and beach characteristics, conservation and urbanization status); (3) determine the influence of environmental (sediment and beach characteristics, conservation and urbanization status) and spatial factors (coasts, beaches, and tidal levels) on the composition similarities of the macrofaunal assemblages. Our data is composed of a matrix containing 224 columns and 140 samples (rows). The first column is a code of each sandy beach; the second column is the sample identity. Column 3 is the name of the sandy beach; column 4 is the coast (Pacific or Caribbean) and column 5 is the level from low tide (I) to high tide (V). Columns 6 and 7 are the geographic coordinates in decimal degrees (latitude and longitude, respectively). Column 8 is the width of the beach in meters and column 9 is the degree of inclination of the beach (slope). The Marine Protected Area status (MPA) is present in the column 10 (1=Protection, 0= non Protection), and the degree of urbanization is indexed in column 11: urbanized with value 3 (in the core of the town: >50% of urbanized area), semi-urbanized with value 2 (in residential areas: <50% and >30% of urbanized area), natural with value 1 (outside the core of the town: <30% of urbanized area) and pristine with value 0, as in Villacampa et al. (2017). Columns 12 to 22 contain the percentage of each sediments fraction in microns of the sand in each sample. The column 23 called "Gravel" is the sum of the fractions 4000, 2000, and 1000 µm, the column 24 called "Coarse" is the sum of fractions 850, 710, 500 and 300 µm. The column 25 called "Fine" is the sum of fractions 250, 125, 63, and 0 (less than 63 µm). Columns 26 and 27 are the mean and median grain size in microns. The columns 28, 29 and 30 are the sorting, skewness, and kurtosis of the sediments, measured following the method of Folk and Ward (1957). Column 31 and 32 are the percentage of total organic matter and carbonates in the sediments, respectively, obtained by the loss on ignition method. Column 33 is the salinity of the marine water at the beach locality. Columns 34 to 224 are macrofauna species (> 500 µm) that live in the sediments. The data in each cell of these columns is the abundance of each species in five corers (20.2 cm2 area or 5.07 cm diameter, and 15 cm deep into the sediment). Columns 34 to 126 are marine worms (annelids and sipunculans), columns 127 to 161 have the abundance of the crustaceans, the insects are in columns 162 to 173, mollusks are in the columns 174 to 199, and the following columns present data from several taxonomic groups.